Population Pharmacokinetics and Exposure‐Response Relationship of Intravenous and Subcutaneous Abatacept in Patients With Rheumatoid Arthritis. (19th September 2018) - Li, Xiaohui; Roy, Amit; Murthy, Bindu
Abstract: Abatacept population pharmacokinetics (PK) and exposure‐response (E‐R) models for selective efficacy end points were developed using phase 2 and 3 study data in patients with rheumatoid arthritis treated with abatacept (intravenous [IV] or subcutaneous [SC]), followed by simulations. Two efficacy end points were assessed in the E‐R analyses: Disease Activity Score in 28 joints (DAS28) and American College of Rheumatology response criteria for 20/50/70% improvement (ACR20/50/70). The analyses were performed with data from 11 clinical studies for the population PK analysis and from 3 clinical studies for the E‐R analyses (DAS28 and ACR20/50/70). The PK of abatacept were time invariant and can be described by a linear 2‐compartment model with first‐order elimination and with zero‐order IV infusion or first‐order absorption for SC abatacept. Baseline body weight was the only clinically meaningful covariate; that is, abatacept clearance and volume of central compartment increased with increasing baseline body weight. Steady‐state trough concentration (Cminss ) of abatacept was identified as the best exposure predictor of DAS28 response compared with other exposure measures. In addition, the E‐R relationship was the same for IV and SC abatacept. Similar results were confirmed in the ACR20/50/70 E‐R analyses. Efficacy responses increased with increasing Cminss and a near‐maximal response was associated with Cminss ≥10 μg/mL. The model‐based analyses confirmed that the weight‐tiered ∼10 mg/kg IV and fixed 125 mg SC abatacept dosing regimens are comparable and achieved plateau responses, by delivering Cminss ≥10 μg/mL in RA patients across all body weights.